(untitled) (Research, Society and Development, 2020)
This article aims to verify the implementation of the National Common Curricular Base and the Law of Directives and Bases of Education, both normative documents, in the panorama of Brazilian basic education, regarding the use and access of technology in the classroom, in addition to compare the application of the guidelines established in current legislation between the public and private educational systems, both in the rural and urban regions of the state of Minas Gerais, in comparison with national indices. The developed research was based, in an exploratory character, in the methodological category of the case study. Concerning the analysis procedures, quantitative methods were explored, about the collection of numerically tangible information collected in the CENSO 2018 database. Throughout this work, there was an explicit inequality between public schools and private schools, mainly in rural areas, where there is little investment presence and public policies focused on education and its maintenance. In this sense, it is concluded that the range and effectiveness of the legal documents, analyzed in this article, are not fully and equally realized in the Brazilian context, especially when it comes to technological resources available for methodological and expository use in the classroom.